Pendekatan Diagnostik Refluks Laring Faring - Rompas, Karin I.; Mengko, Steward K.; Palandeng, Ora Et Labora I. (Universitas Sam Ratulangi, 2021)
Abstract: Lifestyle and behavior changes can have bad impacts on our health. One of the diseases that can be caused by lifestyle changes is pharyngeal larynx reflux. Pharyngeal laryngeal reflux is a state of return of the contents of the stomach to the larynx and pharynx causing an inflammatory reaction to the mucous membranes of the larynx and pharynx. In an attempt to diagnose pharyngeal larynx reflux, a follow-up examination is required. In this case there are several examinations that can be done to confirm the diagnosis of pharyngeal larynx reflux. This study was aimed to obtain the diagnostic approaches in laringopharyngeal reflux cases. This was a literature review study using two databases namely PubMed and ClinicalKey. The keywords used were laringophaingeal reflux and laryngopharyngeal reflux disease. After being selected based on inclusion and exclusion criteria, nine literatures using experimental research methods. were obtained. The results showed that several examinations that could be performed in diagnosing laringofaringeal reflux, as follows: anamnesis, physical examination, pH-monitoring, reflux findings score, reflux symptom score, PEP-test, reflux sign assessment, reflux symptom score, immunohistochemistry, and fiber-optic laryngoscopy. In conclusion, supporting examinations are needed to confirm the diagnosis of pharyngeal larynx reflux.Keywords: refluks laring faring; laryngopharyngeal reflux disease.Â Abstrak: Perubahan gaya hidup dan perilaku dapat berdampak pada kesehatan tubuh. Salah satu penyakit yang dapat diakibatkan oleh perubahan gaya hidup yaitu refluks laring faring. Refluks laring faring merupakan keadaan kembalinya isi lambung ke laring dan faring sehingga menyebabkan reaksi inflamasi pada selaput lendir laring dan faring. Untuk menegakkan diagnosis refluks laring faring dibutuhkan pemeriksaan lanjutan. Penelitian ini bertujuan untuk mengetahui pendekatan diagnosis yang dapat dilakukan dalam pemeriksaan kasus refluks laring faring. Jenis penelitian ialah literature review dengan pencarian data menggunakan dua database yaitu PubMed dan ClinicalKey. Kata kunci yang digunakan yaitu refluks laring faring and laryngopharyngeal reflux disease. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi, didapatkan sembilan literatur yang menggunakan metode penelitian eksperimental. Hasil peneli-tian mendapatkan pemeriksaan-pemeriksaan yang dilakukan dalam menegakkan diagnosis refluks laring faring ialah: anamnesis, pemeriksaan fisik, pH-monitoring, skor temuan refluks, skor gejala refluks, PEP-test, reflux sign assessment, reflux symptom score, immunohistochemistry, dan fiber-optic laryngoscopy. Simpulan penelitian ini ialah pemeriksaan penunjang perlu dilakukan untuk menegakkan diagnosis refluks laring faring.Kata kunci: refluks laring faring; laryngopharyngeal reflux disease